Hoe te denken over woonzorgtechnologie? - Kamphof, Ike (Tijdschrift voor Gerontologie en Geriatrie, 2015)
Bespreking: Alistair Niemeyer. Surveilling autonomy, securing care. Exploring good care with surveillance technology in residential care for vulnerable people Proefschrift. VU Amsterdam, 2015